"King of the zombies" - Purcell, Dick, 1908-1944; Kelso, Edmond (Monogram Pictures Corporation, 1941)
During World War II, a small plane is blown off course by a storm. Guided by a faint radio signal, they crash on an island. The passenger, his manservant and the pilot take refuge in a mansion owned by a doctor. The easily-spooked manservant soon becomes convinced the mansion is haunted by zombies and ghosts. --